2018
DOI: 10.2174/1874467211666180219102520
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 in Radiotherapy: A Potential Target for Radioprotection and Radiosensitization

Abstract: In this review, we describe the role of COX-2 in radiation normal tissue injury as well as irradiated bystander and non-targeted cells. In addition, mechanisms of COX-2 induced tumor resistance to radiotherapy and the potential role of COX-2 inhibition are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 0 publications
1
42
0
1
Order By: Relevance
“…Also, some studies have proposed several agents which inhibit inflammatory and profibrotic pathways to protect or mitigate lung pneumonitis and fibrosis. 25-28 Evidences have shown that inflammatory and profibrotic cytokines play a key role in chronic consequences of exposure to IR in lung tissue. 29 Amongst several cytokines, IL-1, IL-4, IL-6, IL-13, TNF-α and TGF-β are the most effective cytokines in promoting late effects of radiation injury in various organs such as the lung.…”
Section: Resultsmentioning
confidence: 99%
“…Also, some studies have proposed several agents which inhibit inflammatory and profibrotic pathways to protect or mitigate lung pneumonitis and fibrosis. 25-28 Evidences have shown that inflammatory and profibrotic cytokines play a key role in chronic consequences of exposure to IR in lung tissue. 29 Amongst several cytokines, IL-1, IL-4, IL-6, IL-13, TNF-α and TGF-β are the most effective cytokines in promoting late effects of radiation injury in various organs such as the lung.…”
Section: Resultsmentioning
confidence: 99%
“…COX-2 is a key enzyme catalyzing the metabolism of arachidonic acid into prostaglandins and finally contributes to cellular inflammation and carcinogenesis, also involved in RIBE, both in vitro and in vivo [ 23 , 24 ]. Increased COX-2 expression and/or activation in distant non-targeted tissues will cause oxidative DNA damage and elevated cancer risk [ 25 ]. It has been found that COX-2 plays a key role in EMT of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have confirmed that chronic free radical production by irradiated or adjacent nonirradiated cells plays a key role in radiation toxicity [90,91]. Studies have proposed that ROS/NO producing enzymes such as mitochondria, membrane, endoplasmic reticulum and lysosomes in cells, are involved in this process [92]. Modulation of free radical production in these enzymes and organelles have been proposed for amelioration of radiation toxicity [93].…”
Section: Melatonin Modulates Redox Activity Following Exposure To Irmentioning
confidence: 99%